Case Study of Geprek Bensu Franchising Disputes from Intellectual Property Legal Perspective - Urbanisasi Urbanisasi; Hartaty Halim (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
A trademark dispute between Benny Sujono and Ruben Onsu regarding the use of the name "Bensu" in their brand led to a dispute over trademark ownership rights. Benny Sujono, the original owner of the "I Am Geprek Bensu" brand, sued Ruben Onsu at the Central Jakarta Commercial Court regarding the use of the "Bensu" frill in the "Geprek Bensu" brand owned by Ruben Onsu. This dispute reflects the importance of protecting intellectual property rights, including trademarks, in the business world. This case involves a court and a legal process that will determine the ownership rights of the "I Am Geprek Bensu" and "Geprek Bensu" trademarks, as well as whether Ruben Onsu's use of the trademark violates Benny Sujono's ownership rights. The results of this study explain that the settlement of intellectual property rights disputes over the culinary business brand Geprek Bensu with I Am Geprek Bensu based on the Commercial District Court has been decided by decision Number 57/Pdt. Sus. Brand/2019/PN Niaga Jkt Pst.) This trial will play an important role in resolving disputes and determining the ownership rights to the trademarks concerned